Food science and food pocess engineering # Food science and food process engineering Objective Questions & Answers In - Sangamithra, A.; Hemanbika, T.; Chandramohan, K. (Ludhiana Kalyani Publishers Pvt. Ltd., 2019)
Mass Transfer